Increasing Legal Awareness of Child Neglect Crimes by Parents with Increased Legal Awareness - Nawawi, Jumriani; Fadhilah, Nurul; Sulkifly, Sulkifly; Muhaemin, Amril (Al-Bayyinah, 2024)
Law enforcement against the phenomenon of child neglect by parents is a complex problem. Awareness and obedience to the law can be used as a strategy for minimizing child neglect. As a solution in creating the next generation of the nation with superior character and producing quality and moral human resources. The core of the problem carried out in this study is first, identifying the phenomenon of child neglect in Bone Regency, and second, identifying law enforcement efforts against the crime of child abuse by increasing legal awareness. The research methods used are normative juridical and empirical juridical. The results of the study show that neglect of children in Bone Regency is in the form of physical, educational, emotional, and medical neglect caused by the weak influence of the synergy of substance, structure, and culture by Lawrence Friedman's law enforcement theory. Preventive law enforcement efforts for child neglect are carried out by regulations, but repressive efforts from law enforcement are still constrained by public legal awareness of the crime of child neglect. Repressive efforts need strategies to support law enforcement of child neglect crimes by parents in the form of the concept of post-responsibility to realize child protection.